(untitled) (Physical Education, Health and Social Sciences, 2026)
The need for a national rehabilitation policy is underscored by the World Health Organization’s (WHO) emphasis on the critical role rehabilitation plays in global health systems. Rehabilitation is defined by WHO as a set of interventions designed to optimize functioning and reduce disability in individuals with health conditions in interaction with their environment. Globally, about one in three people may benefit from rehabilitation services, underscoring a profound unmet need that affects population health and quality of life. The WHO’s Rehabilitation 2030 initiative reflects a strategic call for action to integrate rehabilitation into health systems comprehensively, promoting accessibility, equity, and sustainability of these services across all life stages. This initiative highlights the necessity of national policies to strengthen rehabilitation governance, service delivery models, workforce development, financing, and research capacity, aligning rehabilitation with universal health coverage and emergency preparedness (WHO, 2023). National rehabilitation policies serve as frameworks to coordinate multisectoral actions, ensuring effective planning, implementation, and monitoring of rehabilitation services to address population needs. Such policies support the removal of barriers faced by people with disabilities, promote inclusivity in public spaces and employment, and foster community-based rehabilitation approaches. Furthermore, these policies help integrate rehabilitation services within primary, secondary, and tertiary healthcare levels, enhancing continuity of care. Given the increasing burden of chronic diseases, aging populations, and the prevalence of disabilities, establishing robust national rehabilitation policies is essential to optimize health outcomes, promote social participation, and improve quality of life for millions worldwide(Ezquerro et al., 2024).